2019
DOI: 10.15252/embj.2018100977
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mitotic checkpoint signaling depends on integrated activities of Bub1 and the RZZ complex

Abstract: Kinetochore localized Mad1 is essential for generating a “wait anaphase” signal during mitosis, hereby ensuring accurate chromosome segregation. Inconsistent models for the function and quantitative contribution of the two mammalian Mad1 kinetochore receptors: Bub1 and the Rod‐Zw10‐Zwilch (RZZ) complex exist. By combining genome editing and RNAi, we achieve penetrant removal of Bub1 and Rod in human cells, which reveals that efficient checkpoint signaling depends on the integrated activities of these proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 69 publications
10
87
0
Order By: Relevance
“…7, A and B;Ishikawa et al, 2005;Tateishi et al, 2013;Mazo et al, 2016). Furthermore, RT-PCR of RPE1 Nek2 KO cells indicated that all sequenced transcripts contained the mutated exon (data not shown), excluding the possibility of exon skipping (Uddin et al, 2015;Rodriguez-Rodriguez et al, 2018;Meraldi, 2019;Zhang et al, 2019). Interestingly, the levels of DAs at interphase centrosomes remained unchanged in ODF2 KO cells ( Fig.…”
Section: Regulation Of Das By Nek2 Does Not Require Odf2mentioning
confidence: 79%
“…7, A and B;Ishikawa et al, 2005;Tateishi et al, 2013;Mazo et al, 2016). Furthermore, RT-PCR of RPE1 Nek2 KO cells indicated that all sequenced transcripts contained the mutated exon (data not shown), excluding the possibility of exon skipping (Uddin et al, 2015;Rodriguez-Rodriguez et al, 2018;Meraldi, 2019;Zhang et al, 2019). Interestingly, the levels of DAs at interphase centrosomes remained unchanged in ODF2 KO cells ( Fig.…”
Section: Regulation Of Das By Nek2 Does Not Require Odf2mentioning
confidence: 79%
“…Of note, we chose to inhibit Bub1 kinase activity instead of depleting Bub1, because Bub1 also has nonenzymatic functions, including the recruitment of mitotic checkpoint proteins to the kinetochore, a function that is maintained after inhibition of its kinase activity (Baron et al, 2016; Meraldi and Sorger, 2005; Raaijmakers et al, 2018; Rodriguez-Rodriguez et al, 2018; Zhang et al, 2019). As previously reported, treatment of cells with the Bub1 inhibitor BAY-320 markedly reduced H2AT120ph and Sgo1 levels at the centromere (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies confirmed a (near)-essential role for BUB1 in the SAC (Meraldi & Sorger, 2005;Klebig et al, 2009), other studies reported no obvious SAC defect in Bub1deficient cells (Johnson, 2004) or showed a SAC defect that could only be observed after sensitization with inhibitors for Mps1 (Vleugel et al, 2015). Recently, Zhang et al combined CRISPR/ Cas9-mediated gene editing with siRNA depletion and concluded that BUB1 also makes a prominent contribution to the SAC in HeLa cells (Zhang et al, 2019). We and others showed that deletion of BUB1 in HAP1 or RPE-1 cells resulted in only a minor SAC defect (Currie et al, 2018;Raaijmakers et al, 2018), while another study showed that (acute) deletion of BUB1 in p53-deficient RPE-1 cells results in a more prominent SAC defect (Rodriguez-Rodriguez et al, 2018).…”
mentioning
confidence: 99%